PENGARUH PERLAKUAN ANNEALING DAN SHOOT PEENING TERHADAP KEKERASAN DAN STRUKTUR MIKRO PADA BAJA KARBON JIS S45C - Bambang Hari Priyambodo; Rizqi Ilmal Yaqin; Margono Margono; Kacuk Cikal Nugroho (P3M Politeknik Negeri Indramayu, 2021)
The industrial world is currently growing rapidly. The need for JIS S45C as a structural steel is increasing which is used to manufacture machine components. Efforts to improve the mechanical properties of steel can use heat treatment and surface treatment. One of the surface treatments that is often used in the industrial world is shot peening. This study aims to determine the effect of annealing and shot peening treatment on S45C steel. The effect of treatment is indicated by changes in the results of both transverse and surface hardness tests and the microstructure of the treatment results. The result is a change in the value of hardness and microstructure changes in JIS S45C from the effect of annealing and shot peening treatments. The highest hardness in the annealing heat treatment and the 15 minute shot peening treatment was 252.08 kgf/mm2. The shot peening treatment causes the grains to become finer from the surface to the subsurface depending on the distance from the surface to the surface depth. These changes cause the surface and subsurface of JIS S45C carbon steel to increase in mechanical properties.